A study on impact of managing employee grievances on employee productivity - SIVANANDAM, DR. PRASANNA; CHATURVEDI, MS. SHUBHEE (The journal of contemporary issues in business and government, 2020)
Employee grievances are considered to be one of the most crucial factors in the workplace. Any workplace which is flooded with grievances have a direct impact on productivity of employees, which ultimately leads to an adverse impact on overall productivity of organisation. This study is to find out the impact of employee grievances on the job productivity and the sample size is 44 which includes the responses of the employees from the following sectors : Information technology, Aviation, Education, Healthcare. Grievances are mostly connected with Compensation, motivating forces, Work pressure and security and if not well taken care of, it will lead to dissatisfied employees who are consistently demotivated and disappointed in their job which ultimately affects the job productivity.